ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN LINEAR SATU VARIABEL KELAS VII SMP NEGERI 3 KOTA SORONG - Melibela, Helena Kateri; Layn, Muhammad Ruslan; Hidayani, Hidayani; Anwar, Zakiyah; Budiarti, Marlinda I.E (Sains Global Institut, Indonesia, 2023)
The research aims to describe the stages of mistakes made by students in solving problems of a system of one-variable linear equations. The research method used in this research is descriptive qualitative. The subjects in the study were class VII students of SMP Negeri 3 Kota Sorong. The research subjects were 27 students of class VII. Researchers divided into 3 abilities, namely (High, Medium, Low) which were taken by 2 from each group so that there were 6 subjects. Data collection was obtained using observation, tests and interviews. Based on Newman's error analysis conducted by the researcher, it can be concluded that 1) students who have high-level abilities always make mistakes at the final stage, namely students do not write conclusions from the problem. 2) students who have medium level abilities always make mistakes at the process skills stage because students are not careful in calculating and at the writing stage of the final answer students are not used to writing conclusions from each question. 3) students who have a low level of ability always make mistakes at the stage of understanding the questions because students cannot write down what is known and what is asked in the questions, errors at the transformation stage because students cannot write down the mathematical model that will be used to solve problems because they do not understand the material at the time it was explained, the error at the stage of processing skills students did not know the method or method used in solving word problems. Then students cannot complete the calculation process because students do not understand the problem in each question. Furthermore, errors in writing the final answer or drawing conclusions students could not do because they were not used to making conclusions because students did not understand the material.